BRICS in a world at crossroads? - Siphamandla Zondi; Norman Sempijja; Thulisile Mphambukeli (Journal of BRICS Studies)
The cross-roads that have been crystallized by global positions on the war in Ukraine reignite the Cold War. The West is united in asserting, sometimes crudely, its geopolitical positions in international affairs. It has over the past decade and a half decided to bring Russia into West’s fold in defence of a US - anchored western international order. Russia has also decided to fight back and assert its independence from this order. In the process, the west has threatened the strategic security of Russia and Russia has also flouted the national sovereignty of its western neighbours that the West tries to use to bring Russia into submission. The expansion of NATO westward, like its expansion south with the invasions of Iraq, Afghanistan and Libya is not an innocent expansion of a regional body but an extension of a highly problematic security complex in defence of Western dominance of the world order.